Issues in development economics - Gupta, Gautam; Gupta, Manash Ranjan; Moitra, Bhaswar (Hyderabad : Orient Longman, 2000)
Contributed articles.
Includes bibliographical references.
Keywords: India -- 1991. -- Economic policy; Economic history